2018
DOI: 10.1051/0004-6361/201732278
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the cloudy atmospheres of HD 209458 b and HD 189733 b with the 3D Met Office Unified Model

Abstract: Aims. To understand and compare the 3D atmospheric structure of HD 209458 b and HD 189733 b, focusing on the formation and distribution of cloud particles, as well as their feedback on the dynamics and thermal profile. Methods. We couple the 3D Met Office Unified Model (UM), including detailed treatments of atmospheric radiative transfer and dynamics, to a kinetic cloud formation scheme. The resulting model self-consistently solves for the formation of condensation seeds, surface growth and evaporation, gravit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
198
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(209 citation statements)
references
References 91 publications
(178 reference statements)
10
198
1
Order By: Relevance
“…The combined effect of a latitudinal temperature variation, set by the preferential energy deposition at the sub-stellar (equatorial) point, and a meridional flow of cloud particles (and metal rich gas) out of the jet and to higher latitudes, resulted in a latitudinal banding of the cloud particles. Lines et al (2018b) also found that their simulations returned an eastwards shift in the peak of the long-wave emission, or hot-spot, qualitatively in line with observations (Knutson et al 2007), alongside supporting turbulent cloud structures stimulating variability in the thermal emission. However, since the atmospheric temperatures for pressures below 1 bar did not exceed the condensation temperature of the mixed-composition silicate cloud, cloud particles were able to form and persist across all longitudes, meaning the simulations did not return a westward shift in the peak short-wave flux, as found in observations (such as the Kepler-7b study of Demory et al 2013).…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…The combined effect of a latitudinal temperature variation, set by the preferential energy deposition at the sub-stellar (equatorial) point, and a meridional flow of cloud particles (and metal rich gas) out of the jet and to higher latitudes, resulted in a latitudinal banding of the cloud particles. Lines et al (2018b) also found that their simulations returned an eastwards shift in the peak of the long-wave emission, or hot-spot, qualitatively in line with observations (Knutson et al 2007), alongside supporting turbulent cloud structures stimulating variability in the thermal emission. However, since the atmospheric temperatures for pressures below 1 bar did not exceed the condensation temperature of the mixed-composition silicate cloud, cloud particles were able to form and persist across all longitudes, meaning the simulations did not return a westward shift in the peak short-wave flux, as found in observations (such as the Kepler-7b study of Demory et al 2013).…”
Section: Introductionsupporting
confidence: 71%
“…Table 1 presents the model parameters for our simulations such as the spatial (vertical and horizontal grid) and temporal (hydrodynamical, radiative and cloud chemistry time-stepping) resolutions, radiative transfer properties, hydrodynamical damping coefficients, the Ackerman & Marley (2001) cloud scheme parameters and a complete list of planetary constants. Apart from the cloud model settings that apply only to this work, all simulation parameters are chosen to match Lines et al (2018b) unless where stated in the following text.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations